Ambulatory Blood Pressure Monitoring Use in the Diagnosis and Management of Hypertension (Journal of Academic Research, 2025)
Background: The classic definition of HTN is based on office blood pressure (OBP) (CBP) measurements, yet The measurements in the office may not reflect the true BP levels.  Ambulatory blood pressure measurement (ABPM) is a non- invasive method for continuous hourly monitoring of blood pressure for 24 hours during patients’ routine activities.Objectives: to evaluate the role of ambulatory blood pressure monitoring (ABPM) in the diagnosis, to guide the accurate management of hypertension and to raise awareness of the benefit using ABPM in the reduction of cardiovascular event, stroke and end-organ damage.Participants and methods: A cohort retrospective study of 208 patients {69 known hypertensive patients on treatment and 139 participants with high office blood pressure measurement, (OBPM)}, at Misurata primary health care clinic. They were referred by their physicians to apply ambulatory blood pressure measurement hourly for 24 hours during the period from January 2022 till June 2023. ABPM results were used to describe patients’ characteristics, different types of hypertensions, the control of the hypertensive state by treatment, and the presence of cardiovascular risk factors, were documented and analyzed.
Keywords: Ambulatory blood pressure; measurements; Libyan population; diagnosis; cardiovascular risk